2016
DOI: 10.1002/cdq.12045
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Career Adaptability From Positive Psychological Traits

Abstract: This study investigated positive psychological traits as predictors of career adaptability in a group of emerging adults. A total of 415 undergraduate students (185 men, 230 women) from a large state‐funded university in Turkey responded to Turkish versions of the Career Adaptability subscale of the Career Futures Inventory (Rottinghaus et al., ), the Dispositional Hope Scale (Snyder et al., ), the Life Orientation Test (Scheier & Carver, ), and the Ego Resiliency Scale (Block & Kremen, ). Results indicated mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
49
0
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(73 citation statements)
references
References 50 publications
13
49
0
9
Order By: Relevance
“…Furthermore, Bozgeyikli and Dog˘an () found that Turkish eighth‐grade students' career development is strongly related to their life satisfaction. Buyukgoze‐Kavas () found a close relationship between Turkish late adolescents' career adaptability and positive psychological variables, such as resiliency, optimism, and hope in life. In a more detailed study with Italian and Swiss adolescents 12 to 16 years of age, Santilli et al () further showed that the existing relationship between career adaptability and life satisfaction is mediated through a positive orientation toward the future.…”
Section: Quality Of Lifementioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Bozgeyikli and Dog˘an () found that Turkish eighth‐grade students' career development is strongly related to their life satisfaction. Buyukgoze‐Kavas () found a close relationship between Turkish late adolescents' career adaptability and positive psychological variables, such as resiliency, optimism, and hope in life. In a more detailed study with Italian and Swiss adolescents 12 to 16 years of age, Santilli et al () further showed that the existing relationship between career adaptability and life satisfaction is mediated through a positive orientation toward the future.…”
Section: Quality Of Lifementioning
confidence: 99%
“…Many researchers support the view that career development is closely related to overall quality of life (Bozgeyikli & Dogan, 2015;Buyukgoze-Kavas, 2016;Hirschi, 2011;Patton, Creed, & Muller, 2002;Santilli, Marcionetti, Rochat, Rossier, & Nota, 2016;Skorikov, 2007). Quality of life denotes subjective satisfaction or feelings of happiness about life (Keyes, 2005).…”
Section: Quality Of Lifementioning
confidence: 99%
“…The process of obtaining hope is considered as constantly evolving and maturing as a discipline and further suggested this could be one of the ways to attain a future scholarship. Hope was also used as a sub-construct in our study, signifying the importance of hope in this aspect [56,57]. Other studies further cemented on the need for training in positive psychology to increase hope among individuals to enable them to set realistic and relevant goals [47].…”
Section: Hope As An Important Component Of Positive Psychological Strmentioning
confidence: 83%
“…Recent research implicates career adaptability as a dynamic mechanism affecting links between dispositional personality traits and career adapting behavior (Nilforooshan & Salimi, 2016). Positive psychological traits involved with hope, optimism, and resilience also show relationships with career adaptability (Buyukgoze-Kavas, 2016).…”
Section: Career Adaptability Through Three Paradigmsmentioning
confidence: 99%